Global shareholder stewardship / edited by Dionysia Katelouzou, King's College London, Dan W. Puchniak, National University of Singapore. - Katelouzou, Dionysia; Puchniak, Dan W., 1976- (Cambridge University Press, 2022)
This is the first in-depth comparative and empirical analysis of shareholder stewardship, revealing the previously unknown complexities of this global movement. It highlights the role of institutional investors and other shareholders, examining how they use their formal and informal power to influence companies. The book includes an in-depth chapter on every jurisdiction which has adopted a stewardship code and an analysis of stewardship in the world's two largest economies which have yet to adopt a code. Several comparative chapters draw on the rich body of jurisdiction-specific analyses, to analyze stewardship comparatively from multiple interdisciplinary perspectives. Ultimately, this book provides a cutting-edge and comprehensive understanding of shareholder stewardship which challenges existing theories and informs many of the most important debates in comparative corporate law and governance.